Factors influencing clopidogrel efficacy in patients with stable coronary artery disease undergoing elective percutaneous coronary intervention: statin's advantage and the smoking "paradox" - Moťovská, Zuzana; Widimský, Petr; Petr, Róbert; Mocová, Danuše; Marinov, Iuri; Šimek, Stanislav; Kala, Petr; PRAGUE-8, Study Investigators (Journal of cardiovascular pharmacology, 2009)
PURPOSE: The aim was to identify factors that influence the efficacy of 600 mg of clopidogrel pretreatment in patients with stable coronary artery disease undergoing elective percutaneous coronary intervention. METHODS: In a laboratory substudy of the PRAGUE-8 trial, the influences of nonmodifiable (age and sex) and modifiable (body mass index and tobacco smoke) factors, comorbidity (hypertension, hyperlipidemia, diabetes mellitus, and renal insufficiency) and cotherapy (statin, aspirin, and heparin), on the course of clopidogrel efficacy were investigated in 105 patients pretreated with clopidogrel >or=6 hours before coronary angiography +/- percutaneous coronary intervention. Flow cytometric analysis of the vasodilator-stimulated phosphoprotein phosphorylation state was used. Independent predictors that influenced clopidogrel action were identified using linear regression. RESULTS: There was no correlation between baseline platelet reactivity index (PRI) and severity of coronary atherosclerosis; mean index of platelet reactivity for a nonsignificant lesion was 72% +/- 5.98% and for a significant lesion 70.08% +/- 8.43%. The highest proportion of low responders was patients with diabetes (50% at 28 hours). Among tobacco smokers, the response to clopidogrel occurred quickly and 80% of smokers had effective inhibition of PRI, 12 hours after drug use. After adjustments, tobacco smoking was an independent predictor for the most robust drop of PRI 12 hours after clopidogrel (P = 0.027). The magnitude of total decrease of PRI at 28 hours was not significantly influenced by cigarette smoking (P = 0.12). Linear regression showed that patients on statin therapy had a better response to clopidogrel than those without statins-the mean decrease of PRI at 28 hours was significantly higher (P = 0.02) among these patients (40.0 vs. 27.6). CONCLUSIONS: In stable coronary artery disease, no correlation exists between baseline PRI and the severity and extent of coronary atherosclerosis. A high loading dose of clopidogrel does not satisfactorily suppress enhanced PRI in patients with diabetes. Cigarette smoking is independently associated with a prompt antiplatelet response to clopidogrel. Ongoing statin therapy is an independent determinant of more effective clopidogrel-mediated inhibition of platelet reactivity.
Keywords: renální insuficience; Ticlopidine; Smoking; hypertenze; Female; fosfoproteiny; hypercholesterolemie; Age Factors; molekuly buněčné adheze; balónková koronární angioplastika; výsledek terapie; ženské pohlaví; Aspirin; heparin; Heparin; kouření; mikrofilamentové proteiny; Diabetes Mellitus, Type 2; věkové faktory; lidé; Phosphoproteins; Platelet Aggregation Inhibitors; diabetes mellitus 2. typu; Treatment Outcome; koronární angiografie; statiny; Humans; Sex Factors; tiklopidin; Hypertension; Hypercholesterolemia; nemoci koronárních tepen; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Aged; sexuální faktory; Cell Adhesion Molecules; index tělesné hmotnosti; Angioplasty, Balloon, Coronary; Coronary Artery Disease; kombinovaná farmakoterapie; inhibitory agregace trombocytů; senioři; mužské pohlaví; Renal Insufficiency; Body Mass Index; Microfilament Proteins; Drug Therapy, Combination; Coronary Angiography